The SERENADE project; a step forward in the safe by design process of nanomaterials: The benefits of a diverse and interdisciplinary approach. (April 2021) - Rose, Jerome; Auffan, Melanie; de Garidel-Thoron, Camille; Artous, Sebastien; Auplat, Claire; Brochard, Gregory; Capron, Isabelle; Carriere, Marie; Cathala, Bernard; Charlet, Laurent; Clavaguera, Simon; Heulin, Thierry; et al.
Abstract: Developing safe nanomaterials has become a major concern in all the industry sectors using advanced materials. However, there are very few initiatives addressing this issue. The SERENADE project, with its long-term funding scheme, provided a unique opportunity to foster a coordinated, yet diverse approach to investigate the safe-by-design development of nanomaterials in a variety of application fields, using a targeted set of inter-disciplinary case studies. The originality of the approach was to cover as many multiple technology readiness levels (TRLs) and life cycle stages as possible, combined with shared hazard and end-of-life assessments in an effort towards a (more) comprehensive and resource driven research. Graphical Abstract: ga1 Highlights: Safe by design of nanomaterials is approached with a set of case studies Case studies are selected to address a wide range of risk reduction strategies. Combining the findings of the set case studies cover the entire life cycle . Sharing hazard and end of life assessment among case studies saves resources.